TRANSFORMASI PELAKSANAAN MAPPETTUADA PADA MASYARAKAT DESA MAJENNANG KECAMATAN SUPPA KABUPATEN PINRANG - Alwi Usra Usman; Darman Manda .; andi ima kesuma (Universitas Negeri Makassar, 2022)
ABSTRACT This study aims to determine: (1) the forms of transformation that occur during the implementation of mappettuada in the people of Majennang Village, Suppa District, Pinrang Regency in the modernization era. (2) the impact of the transformation of the implementation of mappettuada on the people of Majennang Village, Suppa District, Pinrang Regency in the modernization era. To achieve these objectives, the researchers used data collection techniques through observation, interviews and documentation. The data obtained from the research results were processed using qualitative analysis with a descriptive-analytical approach to the transformation of the implementation of mappettuada in the people of Majennang Village, Suppa District, Pinrang Regency. Based on the results of this study, it shows that, (1) There are four forms of transformation that occur during the implementation of mappettuada, namely the exchange of rings, the presence of the prospective bride in the middle of the two family clumps, the use of master of ceremonies and communication (2) the exchange of rings at the time of implementation. mappettuada on the people of Majennang Village, Suppa Subdistrict, Pinrang Regency gave a physical and mental impact to the two prospective brides that they will not turn away from the decisions that have been taken and are ready to bear all forms of risk going forward. The impact of the presence of the prospective bride in the middle of the two family families is that the prospective bride can see the family of the prospective groom who comes to his house during the implementation of the mappettuada. The impact given from the use of the master of ceremony is that the woman must pay for the services of the master of ceremony as a guide for the implementation of the mappettuada. But on the other hand, it also has another impact, namely being able to liven up the atmosphere a little so that both families also know what the arrangement of events is during the implementation of mappettuada. The communication between the prospective groom's family and the bride's family prior to the implementation of the mappettuada had an impact where there was no longer such a thing as a rejected request or no more conflict with one of these transformations.